The impact of COVID-19 upon student radiographers and clinical training. Issue 2 (May 2021) - Rainford, L.A.; Zanardo, M.; Buissink, C.; Decoster, R.; Hennessy, W.; Knapp, K.; Kraus, B.; Lanca, L.; Lewis, S.; Mahlaola, T.B.; McEntee, M.; O'Leary, D.; et al.
Abstract: Introduction: To investigate student clinical placement concerns and opinions, during the initial COVID-19 pandemic outbreak and to inform educational institution support planning. Methods: Between mid-June to mid-July 2020, educational institutions from 12 countries were invited to participate in an online survey designed to gain student radiographer opinion from a wide geographical spread and countries with varying levels of COVID-19 cases. Results: 1277 respondents participated, of these 592 had completed clinical placements during January to June 2020. Accommodation and cohabiting risks were identified as challenging, as was isolation from family, travel to clinical placements, and to a lesser extent childcare. Students stated they had been affected by the feeling of isolation and concerns about the virus whilst on placement. Overall 35.4% of all respondents were 'Not at all worried' about being a radiographer, however, 64.6% expressed varying levels of concern and individual domestic or health situations significantly impacted responses (p ≤ 0.05). Year 4 students and recent graduates were significantly more likely to be 'Not worried at all' compared to Year 2 and 3 students (p ≤ 0.05). The need for improved communication regarding clinical placements scheduling was identified as almost 50% of students on clinical placements between January to June 2020 identified the completion of assessments as challenging. Furthermore, only 66% of respondents with COVID-19 imaging experience stated being confident with personal protective equipment (PPE) use. Conclusion: Student radiographers identified key challenges which require consideration to ensure appropriate measures are in place to support their ongoing needs. Importantly PPE training is required before placement regardless of prior COVID-19 imaging experience. Implications for practice: As the next academic year commences, the study findings identify important matters to be considered by education institutions with responsibility for Radiography training and as students commence clinical placements during the on-going global COVID-19 pandemic.